Amelioration of autoimmune arthritis by adoptive transfer of Foxp3-expressing regulatory B cells is associated with the Treg/Th17 cell balance. Issue 1 (December 2016) - Park, Mi; Jung, Young; Lee, Seon-Yeong; Lee, Seung; Heo, Yu; Kim, Eun; Oh, Hye; Moon, Young; Son, Hye-Jin; Park, Min; Park, Sung; Kim, Ho; et al.
Abstract Background Foxp3 is a key regulator of the development and function of regulatory T cells (Tregs), and its expression is thought to be T cell-restricted. We found that B cells in mice can express Foxp3 and B cells expressing Foxp3 may play a role in preventing the development of collagen-induced arthritis (CIA) in DBA/1J mice. Methods Foxp3 expression was modulated in CD19+ B cells by transfection with shRNA or using an over-expression construct. In addition, Foxp3-transfected B cells were adoptively transferred to CIA mice. We found that LPS or anti-IgM stimulation induced Foxp3 expression in B cells. Foxp3-expressing B cells were found in the spleens of mice. Results Over-expression of Foxp3 conferred a contact-dependent suppressive ability on proliferation of responder T cells. Down-regulation of Foxp3 by shRNA caused a profound induction in proliferation of responder T cells. Adoptive transfer of Foxp3+ CD19+ B cells attenuated the clinical symptoms of CIA significantly with concomitant suppression of IL-17 production and enhancement of Foxp3 expression in CD4+ T cells from splenocytes. Conclusion Our data indicate that Foxp3 expression is not restricted to T cells. The expression of Foxp3 in B cells is critical for the immunoregulation of T cells and limits autoimmunity in a mouse model.